Internationalizing General Education from Within: Raising the Visibility of Heritage Language Students in the Classroom - Evguenia Davidova, PhD (Park University, 2011)
This article analyzes the findings of a pilot project conducted in 2008-2009 as a partnership between University Studies, Portland State University's interdisciplinary general education program, and the University's Russian Flagship Language Partner Program. The project proposes a new approach of integrating non-English speakers' language skills, culture, and life experiences into classroom activities of general education courses. By engaging the students as facilitators in the exploration of their own cultures and languages, the project offers a model of enriching collaborative student teaching and learning that could be applied to various interdisciplinary courses.